Assessing the needs of grandparents of preterm infants in neonatal intensive care units: a cross-sectional study - Huang, Huamin; Tao, Jingyun; Lei, Ying; Chen, Rui; Fang, Haixia (Frontiers in Psychology, 2024)
Background Globally, there is an increasing trend in the incidence of premature births and low birth weight. Neonatal intensive care unit (NICU) care has become indispensable for these newborns. Nevertheless, this mode of care poses substantial economic, psychological, and health challenges to the families of preterm infants. Despite abundant evidence concerning the parents’ needs in the NICU, the needs of grandparents—vital family members—are frequently disregarded. This exploratory study aimed to assess the grandparents’ needs of preterm infants in the NICU, exploring the impact of demographic elements on these needs to offer guidance for clinical care practices. Methods This study employed a cross-sectional design and the Chinese version of the NICU Family Needs Inventory (NICU-FNI) to investigate the needs of grandparents. A total of 280 grandparents participated in the study, providing data by completing structured questionnaires related to their demographic profiles and needs. Statistical analyses were utilized to analyze the data, including descriptive statistics, chi-square tests, Pearson’s correlation, and multiple linear regression. Results Six items about Assurance emerged as significant among the top 10 important needs, with two items for Information, one for Proximity, and one for Support; among the least important needs, nine items related to Comfort and Support were identified. The subscale “Assurance” achieved the highest mean score of 4.07 ± 0.49, followed by the subscales of “Information” and “Proximity,” registering mean scores of 3.50 ± 0.47 and 3.50 ± 0.46, respectively. This explorative study identified a correlation between the needs for Assurance and employment status, place of residence, gestational age, and birth weight (p < 0.05). Employment status, place of residence, and gestational age were identified as significant correlates for Assurance (p < 0.05). Conclusion The foremost need identified by grandparents is Assurance of quality care for preterm infants, closely followed by the demand for thorough Information and the ability to be in Proximity to the infant. This exploratory study highlights that mitigating the strain on families with preterm infants, as well as recognizing and meeting the needs of grandparents, is of paramount importance.